Kaunas Hard Labour Prison in the Years of Nazi Occupation (1941–1944) - Bubnys, Arūnas (Genocidas ir rezistencija, 2009)
At the beginning of the war and Nazi occupation, with the efforts of the recreating Lithuanian administration, the system of prisons and forced labour camps, which operated in the years of the Republic of Lithuania and Soviet occupation, was renewed. A big part of the prison staff members from the years of independent Lithuania who in the Soviet period were massively discharged from their workplaces returned to their places of work. At the beginning of August 1941, with the establishment of the German civil power, the exclusive right to govern the prisons and to supervise them was granted to Adrian Theodor von Renteln, the German General Commissar for Lithuania. The occupational Nazi authorities commissioned their own German commissars and commandants to the major prisons of the Lithuanian general territory prisons (including also the Kaunas Hard Labour Prison). The Nazi officials were the true governors of the imprisonment facilities and controlled the work of the Lithuanian administration of prisons. The Kaunas and Vilnius (Lukiškės) hard labour prisons were the major prisons in the occupied Lithuania. The political and criminal prisoners of various nationalities and of different ages were imprisoned in the Kaunas Hard Labour Prison (KHLP). In the first days of the Nazi occupation, the majority of the convicts in the KHLP were of Jewish nationality. In July 1941, in the Seventh Kaunas Fort, after the Jews were shot, until the very end of the Nazi occupation, the major part of the prisoners consisted of the Lithuanians, with Russians also constituting quite a substantial part. The composition of the prisoners from the autumn of 1941 until the end of the occupation reflected in the essence the composition of Kaunas city and district population by nationality (the left alive Kaunas Jews were imprisoned in the Kaunas Ghetto). The greater part of the prisoners was usually constituted not of those punished and serving the punishment but rather of the prisoners under interrogation. The convicts who were at the disposal of the German Security Police and SD most often were imprisoned in separate cells. The conveyance of those prisoners to the German security bodies most often meant that they were taken away to be shot.